An Evaluation Of Human Resource Roles: A Case Study Of Gas Malaysia Sdn Bhd. - Mohamed, Normala (2002)
The Human Resource department of Gas Malaysia is in the process of transforming itself from being primarily an administer/transaction processor for basic human resource functions (such as compensation payment, benefits administration, record keeping) to being a business partner to the other departments in Gas Malaysia by helping to increase the value they can derive from their current, and planned, stock of human assets. The first part of this paper identifies four elements within Gas Malaysia hypothesized to affect user department satisfaction. We call these the components of internal service quality. By measuring these components, Human resource Manager is able to determine which actions are required to improve customer satisfaction. This knowledge may then enable the manager to take a proactive, rather than reactive , approach to customer satisfaction.